Cancer Therapy: Diamond‐Lipid Hybrids Enhance Chemotherapeutic Tolerance and Mediate Tumor Regression (Adv. Mater. 26/2013). (8th July 2013) - Moore, Laura; Chow, Edward Kai‐Hua; Osawa, Eiji; Bishop, J. Michael; Ho, Dean
<x xml:space="preserve">Abstract</x> To facilitate targeted drug delivery using nanodiamond (ND) vehicles, epirubicin‐functionalized ND/lipid hybrids are coupled to epidermal growth factor receptor (EGFR) antibodies. The resulting particles mediate tumor regression, and markedly improve drug tolerance in a triplenegative breast cancer model in vivo. Furthermore, comprehensive biocompatibility analysis following intravenous ND administration indicate that the particles are well tolerated by mice. Further information can be found in the article by Dean Ho and co‐workers on page 3532. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>